Digital marketing strategy in increasing brand awareness of technology startups - Popo Suryana (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2024)
Startups in the technology sector often face challenges in introducing their brands in a competitive market. Therefore, this research will explore various digital marketing approaches and strategies that can help technology startups to increase their brand awareness levels. Qualitative research methods with a descriptive approach were used in this research. The research results show that digital marketing strategies, including search engine optimization, quality content, collaboration with influencers, and digital advertising, play a crucial role in increasing brand awareness for technology startups. By focusing on the target audience, creating relevant content, and interacting through social media, startups can achieve greater exposure. Collaborations with influencers and digital advertising help introduce brands to established audiences, while rigorous data analysis supports informed decision-making. As a result, digital marketing becomes a strong foundation in building brand awareness, helping startups to compete and grow in a competitive business environment.